Entre vidas e negócios: Um estudo das competências empreendedoras de médicos empreendedores - SILVA, Henrique Henrique Pereira da (2023)
Focusing on the healthcare context, this study aims to investigate the relationship between the stages of physicians' entrepreneurial process and their entrepreneurial ompetencies. The entrepreneurial process stages were identified based on Baron and Shane (2007), and the entrepreneurial competencies were determined according to Cooley's theoretical model (1990). This study is justified by the relevance of the medical field in society, coupled with the role of the healthcare industry and the development of physician entrepreneurship in clinics, medical centers, startups, and other healthcare-related businesses, as well as the theoretical and empirical gap in studies linking entrepreneurship to the medical field. A qualitative and descriptive research approach was employed, involving semi-structured interviews with nine physician entrepreneurs. Content analysis was used for data treatment, and the ATLAS.ti 23 software assisted in data coding. The results indicate that some physicians followed the stages sequentially, from idea generation to successful business consolidation, particularly those who have been in business for a longer time. However, others did not strictly adhere to the stages, especially those who inherited the business through family influence. Regarding entrepreneurial competencies, several relevant competencies were highlighted in the achievement (demand for quality and efficiency, persistence, and commitment), planning (information search), and power (persuasion and networking) groups. A significant coexistence was observed between the stages of physicians' ntrepreneurial process and their entrepreneurial competencies. Competencies such as persistence, independence, self confidence, persuasion, and networking were considered essential for physicians' entrepreneurial success, particularly in the initial and final stages of the process. Additionally, digital competencies emerged as an important empirical category, with social media platforms being identified as powerful tools for marketing, entrepreneurship, and customer acquisition. The central contributions of this study lie in deepening the understanding of physicians' entrepreneurial process stages and competencies, the relevance of these aspects in their entrepreneurial context, advancing the theoretical and empirical knowledge in this field, and the identification of an category that emerged from the research findings.